Language Policy of Ukraine: Major Results - E. A. Markova (Проблемы постсоветского пространства, 2020)
In its almost three decades history, Ukrainian language policy has gone through several stages of its development. Formed before the collapse of theUSSR, the Ukrainian elite actively used the issue of the language to achieve its political goals. Even at the turn of the 80-90s of the last century, the issue on the status of the Russian language was in the focus of the political struggle. Relying on the party and bureaucratic apparatus support, the nationalistically-spirited elite ofUkrainebegan to use the language issue for winning over the population of the southeastern regions. At that time, it was of great importance, since before the collapse of theUSSR, the Ukrainian elite was interested in preventing the growth of protest sentiment within the country. In subsequent years, the issue of the Russian language status has repeatedly become the subject of intense political battles and speculation as well. The Party of Regions, the Communist Party exploited the theme of “protecting” the Russian language to consolidate their electorate before the parliamentary and presidential elections. Concurrently, the Western Ukrainian elites defended a different position, proposing to expand the scope of the Ukrainian language while at the same time confine the Russian language.Despite the turmoil between the Western Ukrainian and Eastern Ukrainian elites, especially during the pre-election periods,Ukrainegradually “drifted” towards restricting the use of the Russian language and expanding Ukrainian in education and culture.The situation in the linguistic sphere inUkrainechanged dramatically after 2014, when representatives of nationalist forces came to power. It became a policy to revise the legislation governing on the use of languages of national minorities, to which the Russian language began to fall into. As a result, the possibilities for using the Russian language were confined, while enhancing the role of the Ukrainian language. This situation has already aggravated the relations betweenUkraineand neighboring countries, in which they negatively evaluatedUkraine’s policy in the language sphere. In addition, limited scope for the Russian language has ratcheted up tension within the country, provoking new inter-regional contradictions.